Tectonic In Architecture - Ali Mohsen Al-Khafaji (Iraqi Journal of Architecture and Planning, 2018)
Architectural development along its history reflects advancement of expression ability of ideas , elements and structural systems . This explain how a specific structural system gains specific aesthetic values which obtained by cumulative experts advice about construction and architecture , also explain the convertibility of constructional thought pure structural system into structural system tectonic .The research problem was the lake of knowledge about complex degree of tectonic consept and its correlation with the structural system and construction . From this point, the comprehensive understanding of a tectonic concept depends on understanding the essential nature of structural system and construction as long as with functional space (closed and semi - closed) and gets through with functional structure and aesthetical needs without omitting theethical role in composing architectural and structural coherence which is the main researchaim . The research methodology consist of three stages ; First, construct operational definitionof tectonic concept. Second, investigate about â€œ Tectonics â€ as â€œ Tectonicconstruction â€ throughout two levels ; first descriptive concern with corporeal , physical ,formal characteristics and the second analytical /descriptive concern with incorporeal,aesthetical, ethical, in the last level it was analyzed many projects depending on mainconcepts deduct from previous knowledge . The final stage are determines the main researchconclusions .Key words : tectonic, form, force, construction, space, aesthetical, ethical .